O processo de (re)produção das notícias nos sites jornalísticos da Paraíba: análise dos releases enviados pela Ascom/UFCG - Mendes, Gloriquele da Silva (2015)
This study aims to analyze the process of reproduction of reports in the news sites of Paraiba - G1 PB, ParaíbaOnline and Iparaíba - from releases sent by the Federal University Communications Department of Campina Grande (UFCG). To conduct the survey was done a literature and documentary sources on Media Relations, Journalism Theories, Digital Journalism, newsworthiness criteria, among others was carried out yet, a survey of releases sent to the media and published in the media. Once this step, visits were made to the surveyed sites and interviews with journalists these vehicles to meet the production routine of writing, and to investigate if there was a line or discrepancy between what journalists claiming to make the placement of the news and what actually had been observed by us in the previous survey. The research is quantitative and qualitative. Its quantitative character is presented in the observation made during the months of November 2013 and November 2014 of releases sent by Ascom UFCG. Data were categorized into subjects that most fascinate the media and the least attract the interest of journalists. It was also an analysis of the impact of propagation and reproduction of releases by news sites. The qualitative research approach will be in the detailed study of the phenomenon, in which we try to explain the characteristics and contexts in which they are the object of research. The study has helped understand the reality of digital journalism newsrooms, in particular, working in the city of Campina Grande, as well as reflect on the role of journalists and advisors in the current situation where practices and journalistic functions are constantly changing and being reconfigured .